(untitled) (Journal of Tikapur Multiple Campus, 2014)
The main purpose of the study is to find out the prevalence of tuberculosis in the community. This study provides data to generate a demographic and socioeconomic profile of the population in sixteen villages of the Devdaha VDC. Secondary data were collected from the District Health Office (DPHO) and National Tuberculosis Centre (NTC). On the basis of community survey, the prevalence rate in the year 2004 was 3.88 per thousand persons. It was also found that the number of TB cases varied from the rich economic category, 0.93 per thousand in the middle and 19.52 per thousand among very-poor section of the population. This study also shows that estimated sputum-positive TB cases of prevalence rate ranged from 3.00 to 11.60 per thousand. Prevalence of all forms of TB in Rupandehi district is estimated to range from 12.59 to 48.74 per thousand using community survey data and available studies.